A randomized, double‐blind, placebo‐controlled, multiple dose, parallel study to investigate the effects of a cathepsin S inhibitor in celiac disease - Darren Bentley; Marie Mannino; Marianne Manchester; Priscila Camillo Teixeira; Bernhard Reis; Malcolm Boyce; Sandra Nagel (Clinical and Translational Science)
Abstract Celiac disease is a chronic, immune‐mediated enteropathy with symptoms triggered by exposure to dietary gluten in genetically predisposed individuals. The only available management option is lifelong adherence to a gluten‐free diet. This randomized, double‐blind, placebo‐controlled, parallel‐group, single‐center study tested the effects of the cathepsin S inhibitor RO5459072 on the immune response to a 13‐day gluten challenge in 19 participants with celiac disease (ClinicalTrials.gov: NCT02679014). Nine participants in the RO5459072 arm received 100 mg study drug b.i.d. (200 mg daily); 10 received a placebo. The primary end point was the number of responders to the gluten challenge (defined as individuals with an increase in the number of gliadin‐specific, IFNγ‐secreting T cells detected using an ELISPOT assay). However, there was a weak response to the gluten challenge across both arms. Few participants had an increase in gliadin‐specific, IFNγ‐secreting T cells, and the antigen‐specific responses (anti‐tTG and anti‐DGP antibodies) were weaker than expected in both arms. Therefore, the primary end point was not met, although the study was underpowered to detect a treatment effect under these circumstances. Pharmacodynamic findings suggested that RO5459072 had some beneficial effects. Fewer participants in the RO5459072 arm exhibited gliadin‐specific IFNγ‐secreting T cells after 6 days' gluten intake. Participants in the RO5459072 arm also showed decreased intestinal permeability, and a decrease in the number of circulating B cells, CD4+ and CD8+ T cells compared to baseline. Nevertheless, the absence of clear effects on the response to a gluten challenge indicates that inhibition of cathepsin S may not be an effective treatment strategy for celiac disease.